Law as a Tool for Preventing Chronic Diseases: Expanding the Spectrum of Effective Public Health Strategies - George A. Mensah; Richard A. Goodman; Stephanie Zaza; Anthony D. Moulton; Paula L. Kocher; William H. Dietz; Terry F. Pechacek; James S. Marks (Centers for Disease Control and Prevention, 2004)
In part one of this 2-part series, we reviewed the important roles that laws have played in public health and provided examples of specific laws and their effectiveness in supporting public health interventions (1). We suggested that conceptual legal frameworks for systematically applying law to preventing and controlling chronic diseases have not been fully recognized and we provided the basic elements of a conceptual legal framework. In part 2 of this series, we first provide an overview of U.S. jurisprudence, describe the legal mechanisms, remedies, and tools for applying law to public health, and summarize the jurisdictional levels at which laws, mechanisms, remedies, and tools operate. We then identify the potential contours for legal frameworks of varying complexity and scope by offering examples of legal frameworks in public health practice. This paper also outlines a plan for increasing the capacity within the Centers for Disease Control and Prevention (CDC) for developing legal frameworks and expanding guidance on using legal tools for preventing and controlling chronic diseases. Finally, we describe resources for building or enhancing the capacity to use law as a tool for preventing diseases, injuries, and disabilities at the local level.